1993
DOI: 10.2307/1542222
|View full text |Cite
|
Sign up to set email alerts
|

Ooplasmic Segregation in the Medaka (Oryzias latipes) Egg

Abstract: Using time-lapse video microscopy, we found that ooplasmic inclusions in the fertilized medaka egg displayed two types of movement during ooplasmic segregation. The first manifested itself as the movement of many inclusions (diameter = 1.5-11 μm) toward the animal pole at about 2.2 μm min-1; this type of movement appeared to be streaming. The second type of movement was faster (about 44 μm min-1) and saltatory; inclusions displaying this type of movement were smaller (diameter ≤1.0 μm) and moved toward the veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 48 publications
(31 reference statements)
1
31
1
Order By: Relevance
“…21 Therefore, our result can be interpreted as showing that the cytoplasm is rich in glycogen and the materials in the cytoplasm are collected from all around the egg yolk aer fertilization. This was conrmed using Raman spectra, which showed that the averaged concentration of glycogen in the yolk during Stages I-IV was lower than that in Stage 0.…”
Section: Resultsmentioning
confidence: 74%
“…21 Therefore, our result can be interpreted as showing that the cytoplasm is rich in glycogen and the materials in the cytoplasm are collected from all around the egg yolk aer fertilization. This was conrmed using Raman spectra, which showed that the averaged concentration of glycogen in the yolk during Stages I-IV was lower than that in Stage 0.…”
Section: Resultsmentioning
confidence: 74%
“…A transient 'contractile wave' of cortical cytoplasmic layer follows the wave of exocytosis (Iwamatsu, 1973;Iwamatsu and Hirata, 1984). Due to the oscillatory contractions following this distinct contractile wave, the cortical cytoplasm progressively accumulates toward the animal pole to form a thick cytoplasmic layer (Abraham et al, 1993;Sakai, 1964). At 7 -8 min after sperm entry, the second polar body is extruded onto the surface of the cytoplasm at the center of the area where the germinal vesicle broke down during oocyte maturation.…”
Section: Stage 1 (3 Min) Activated Egg Stagementioning
confidence: 99%
“…Like in Drosophila , embryonic droplets in many species are highly motile: for example, lipid droplets in both mouse and fish embryos display active motion dependent on the cytoskeleton [92, 94], and for fish, annelids, and moths, massive redistribution of the droplet population accompanies early development [95, 97, 98]. Very little is known about mechanism and function of droplet motility in these species.…”
Section: Introductionmentioning
confidence: 99%